Analysis Of The Structure And Function Of Madrasas As Social Institutions In Islamic Society (Case Study In Madrasah Tsanawiyah (Mts) Insan Cendekia Sangatta Utara, East Kutai) - Selvi Dewi Rahayu; Muhammad Yasin (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This research aims to analyze the structure, function, and interaction of madrasah as a social institution in Islamic society, with a case study at MTs Insan Cendekia Sangatta Utara. Data were collected through interviews, observations, and document analysis, then analyzed thematically with triangulation to ensure validity. The results show that the madrasah has a well-organized organizational structure, supporting its social and religious functions. The main functions of the madrasah include the integration of formal education with Islamic values, character building, and strengthening spirituality. The social function is realized through religious programs and social activities. The study concludes that madrasahs not only provide formal education, but also act as social institutions that support character development and Islamic values in society.